Autonomous Fuzzy Control and Navigation of Quadcopters. Issue 5 (2016) - Domingos, Diego; Camargo, Guilherme; Gomide, Fernando
Abstract: A quadcopter is a multirotor helicopter lifted and propelled by four rotors. Classic and fuzzy controllers have been used for stabilization and navigation control of quadcopters, but they require considerable effort to design and tune their parameters. Controller tuning can be a challenging task especially when random environment and load disturbances are of major concern. This paper addresses the design and evaluation of a parameter free self evolving quadcopter autonomous fuzzy system for stabilization and navigation control of quadcopters. Simulation results suggest that the autonomous fuzzy control system outperforms classic fuzzy control.